The Effects of Limited Dining Area in Bestlink College of the Philippines School Canteen: Basis for Action Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Colleges do everything to attract top students, providing quality academic programs inaddition to residential and social facilities that make campus life more enjoyable. Every schoolcanteen faces the same issue: not enough space to accommodate consumers during lunch orrecess. Limited meal options. The terrible line at the canteen. When there are long lines, goingto the canteen may appear to be a pleasure but is usually a chore. You need to create awelcoming and comfortable environment that tempts individuals to dine there during breaks.Canteens are where your students and employees will gather during breaks, so it is importantto ensure that the spaces are welcoming and complement the school's aesthetic.Most of the respondents are female, and also most of the respondents are from the 2nd-yearlevel. The level of satisfaction of students in the school canteen was based on the canteenfacilities, dining area, and ventilation. On the other hand, there are problems encountered bythe respondents on limited dining space as well as limited choices of food, lack of canteenmaintenance, unclean tables and chairs, and lack of trash bins.The researchers would like to recommend that the school canteen administration add morestalls for more food choices for the students. The researchers would like to recommend thatthe school canteen administration provide school canteen maintenance. The researcherswould like to recommend that future researchers know the importance of research not onlywithin the school but also in other aspects connected to the dining area.
Keywords: Business